Sports facilities development towards sustainable community: A case study of Kuala Lumpur - Barghchi, M.; Omar, D.; Aman, M.S. (2010)
Sports and sports facilities development have improved rapidly over the past years in Malaysia. However, such improvements are inadequate compared to the overall development of sports at international level. In recent years sport is getting more and more influential and it will continue to grow in importance, even for developing countries. Increase in the amount of public money being spent on sports facilities, at the same time, increase in the number of sports facilities as well as increasingly importance of sustainability necessitate demand to investigate issues surrounding sports facilities development especially in Kuala Lumpur as the regional and national centre for sporting activities. The long-term benefits to cities and local communities need to achieve more initiative by decision-makers. However, sustainability is more important for sports facilities due to requirement of huge money for construction, ancillary needs and constant maintenance costs. This research aims to examine the effectiveness and intangible benefits of sports facilities in Kuala Lumpur through residents' perceptions. Four case studies each selected from one of the four managing zones of sports facilities developed by Kuala Lumpur City Hall provide information for this research. The research able to rank the case studies based on residents' perception towards their attitude about facilities and programmes, using of the facilities, and respondents’ willingness to pay. The paper argues that the sports facilities could only have limited impacts on residents which need to improve and increase the impacts for further development.